Penguatan Koperasi Kartini Mandiri Lestari Desa Pasarean Kecamatan Pamijahan Kabupaten Bogor - Setiawan, Rudi; Ramayanti, Rizka (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Cooperatives as joint business units owned by their members certainly require good and transparent management, cooperative managers should play an active role in carrying out their role of fostering their members so that they can progress and grow together in building a business. Throughout the establishment of the kartini mandiri lestari cooperative, there are still a number of challenges faced including technical operational problems in the Cooperative which are still carried out manually, another challenge comes from the lack of knowledge of cooperative members' business management so that the business that is built tends to not last long. In this community service activity efforts are made to solve problems that exist in the kartini mandiri lestari cooperative with activities in the form of socialization, training, assistance and implementation of cooperative applications as well as monitoring and evaluation of each activity. The results of the evaluation of the socialization activities for the preparation of financial reports and production costs stated that there had been an increase in participants' understanding by 74.07%, while the assessment of user interpretations of cooperative applications reaches 80% in the category of feasible implementation.